Unraveling Supply Chain Ambidexterity: A Synthesis of Theoretical Development and Empirical Insights - Hasemy Rafsanjani; Iwan Vanany (Dinasti Publisher, 2025)
Supply chain ambidexterity (SCX), A strategic approach to balance exploration and exploitation within supply chain operations, has emerged as a critical capability in dynamic and competitive business environments. This study presents a systematic literature review (SLR) to synthesize existing theoretical developments and empirical findings on ambidexterity approach in the field supply chain. Drawing from 202 peer-reviewed articles published between 2015 and 2025, this review identifies the key themes, theoritical progressions, key dimensions, and performance implications associated with SCX. The analysis reveals that SCX has evolved from a loosely defined concept to a structured multidimensional construct, commonly measured through capabilities, and strategic orientations. Empirical studies confirm a positive association between SCX and firm performance, particularly in terms of adaptation, innovation, and resilience. However, the review also uncovers trade-offs, such as resource constraints and structural misalignments, which challenge firms attempting to implement SCX effectively. Furthermore, the review reveals variation in how SCX is conceptualized through its key dimensions, and identifies a lack of longitudinal studies examining its development over time. By integrating theoretical and empirical perspectives, this study contributes a comprehensive understanding of SCX and proposes directions for future research, including cross-industry comparative analysis, dynamic capability integration, and context-sensitive SCX frameworks. The findings aim to support both scholars and practitioners in advancing the strategic deployment of SCX.